Ficus trees in rainfed agricultural systems of Karnataka, southern India: An analysis of structure, benefits, and farmers’ perceptions - Dhanya, B.; Viswanath, Syam; Purushothaman, Seema (Journal of Tropical Agriculture, 2012)
Ficus spp. are abundant in the rainfed agricultural areas of southern Karnataka, especially in Mandya district, often in association with field crops. We describe here the structure of this less documented traditional agroforestry system and elicit the farmers’ perceptions. Farmer interviews, village level group discussions, and field-walks were conducted to garner information on various aspects of Ficus planting in 18 villages of Mandya district. In the rainfed agricultural systems of the study area, Ficus trees provide fodder, shade, and fuelwood, besides performing environmental service functions such as supporting soil fertility and biodiversity conservation. The paper highlights the indigenous knowledge base and skills of farmers and the mutualistic linkages between components contributing to sustainability of the system.